2022
DOI: 10.1038/s41598-022-22354-2
|View full text |Cite
|
Sign up to set email alerts
|

Volatile compounds of Bacillus pseudomycoides induce growth and drought tolerance in wheat (Triticum aestivum L.)

Abstract: The plant growth-boosting biofilm-forming bacteria Bacillus pseudomycoides is able to promote growth and drought stress tolerance in wheat by suppressing the MYB gene, which synthesizes Myb protein (TaMpc1-D4) through secreted volatile compounds. In the present study, Triticum aestivum seeds were inoculated with five distinct bacterial strains. The growth, germination rate, root-shoot length, RWC, and chlorophyll content of seedlings were investigated. Furthermore, the levels of soluble sugars, proteins, H2O2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 87 publications
(69 reference statements)
0
9
0
Order By: Relevance
“…The study used an RCBD (randomized complete block design) with three replications for each biological sample [33]. A two-way ANOVA was conducted, employing Duncan's multiple range test (DMRT), with a significance level set at p ≤ 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…The study used an RCBD (randomized complete block design) with three replications for each biological sample [33]. A two-way ANOVA was conducted, employing Duncan's multiple range test (DMRT), with a significance level set at p ≤ 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Yue et al (2019) indicated that B. altitudinis WR10 increased the germination rate of wheat seeds under salinity stress (200/400 mMNaCl), mostly because of osmolytes secretion, bio lm formation, and by the synthesis of enzymes including catalase, amylase, and ACC deaminase. Meanwhile, it has been proven that volatile organic compounds generated by Bacillus strains stimulated seed germination and seedling emergence (Ramirez et al 2020;Paul et al 2022). Interestingly, Lastochkin et al (2020) found that B. subtilis 10 − 4 alleviated the passive effect of PEG-6000 seed germination of wheat (Triticum aestivum) cv.…”
Section: Discussionmentioning
confidence: 99%
“…The process that occurs is that Bacillus pseudomycoides bacteria suppress the MYB gene, which synthesizes the Myb protein (TaMpc1-D4) through volatile compounds released. These compounds could induce growth and defend plants from drought stress [21]. Both bacteria effectively inhibited the growth of fusarium wilt disease in banana plants [6] Ma01_g01890 gene acts as a transporter of 1-6 inorganic phosphate, Ma03_g26260 acts as a transporter of 1-11 inorganic phosphate, and Ma04_g36790 acts as a transporter of 1-4 inorganic phosphate in banana barangan (Musa acuminata) plants.…”
Section: Discussionmentioning
confidence: 99%